2021
DOI: 10.1177/01445987211023854
|View full text |Cite
|
Sign up to set email alerts
|

The link between urbanization, energy consumption, foreign direct investments and CO2 emanations: An empirical evidence from the emerging seven (E7) countries

Abstract: This study investigated the link between energy consumption (EC), foreign direct investments (FDI), urbanization (URB) and CO2 emissions in the emerging seven (E7) countries for the period 1991 to 2014. The exploration made a methodological contribution by employing modern econometric methods that are robust to the issues of cross-sectional dependence and slope heterogeneity, so as to obtain valid and reliable outcomes. From the results, the panel under consideration was heterogeneous and cross-sectionally cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 98 publications
0
12
0
1
Order By: Relevance
“…As a result, it is vital to segregate them and safeguard the conventional sources key-ins to grow E.E. and reduce emissions ( 33 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, it is vital to segregate them and safeguard the conventional sources key-ins to grow E.E. and reduce emissions ( 33 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Se plantea un modelo empírico para los determinantes de las emisiones territoriales de CO2 per capita en Ecuador. Comúnmente, las emisiones de CO2 per capita recogen el impacto ambiental, puesto que suele evaluar eficazmente el desempeño del medio ambiente (Li et al, 2021;Rahman, 2019). El modelo también permite comprobar la existencia de la CKA, conforme la siguiente formulación estándar en economía energética (Halicioglu, 2009):…”
Section: Metodologíaunclassified
“…Haldar and Sharma (2022) discovered evidence in support of the increased energy demand resulting from urban population growth to promote CO 2 emissions in India over the period 1960–2015. Li et al (2022a, 2022b) found evidence in support of balancing growth in low-income SSA countries with energy-growth SDG-7 objective over the period 1995–2016. Salahuddin et al (2019a, 2019b) uncovered a significant short-run and long-run relationship between urban population growth and CO 2 emissions in South Africa over the period 1980–2017.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has documented studies on the subject matter, but the closest study that is positioned to the current study (Udemba and Keleş, 2022; Anwar et al , 2022; Dieudonné and Aristophane, 2021; Haldar and Sharma, 2022; Li et al , 2022a, 2022b; Salahuddin et al , 2019a, 2019b). Udemba and Keleş (2022) uncovered the positive link between urbanization, economic growth and CO 2 emissions in Turkey over the period 1970–2018 using auto-regressive distributed lagged (ARDL) models.…”
Section: Introductionmentioning
confidence: 99%